2021
DOI: 10.3390/soilsystems5020026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plant Growth-Promoting Traits and Inoculation Effects on Triticum durum of Actinomycetes Isolates under Salt Stress Conditions

Abstract: This study aimed to characterize the halotolerant capability, in vitro, of selected actinomycetes strains and to evaluate their competence in promoting halo stress tolerance in durum wheat in a greenhouse experiment. Fourteen isolates were tested for phosphate solubilization, indole acetic acid, hydrocyanic acid, and ammonia production under different salt concentrations (i.e., 0, 0.25, 0.5, 0.75, 1, 1.25, and 1.5 M NaCl). The presence of 1-aminocyclopropane-1-carboxylate deaminase activity was also investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 93 publications
1
9
0
Order By: Relevance
“…On the contrary, plants under salt stress inoculated with B. ambifaria and H. seropedicae showed a reduction in chlorophyll content but an enhancement in carotenoids (Table 3). Our results are in accordance with previous studies that showed an increase, compared with saline control, in the amount of chlorophyll and carotenoids in plants of Brassica napus [52] and Triticum durum [50] exposed to salt stress and inoculated with PGPB strains. The increase in photosynthetic pigments in PGPB-inoculated plants suggests the capacity of bacterial inoculation to reduce the detrimental effects of salt, by ameliorating the activities of electron transporters associated with photosynthesis [60], as well as the biosynthesis of proteins and enzymes related to pigment stabilization [61].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the contrary, plants under salt stress inoculated with B. ambifaria and H. seropedicae showed a reduction in chlorophyll content but an enhancement in carotenoids (Table 3). Our results are in accordance with previous studies that showed an increase, compared with saline control, in the amount of chlorophyll and carotenoids in plants of Brassica napus [52] and Triticum durum [50] exposed to salt stress and inoculated with PGPB strains. The increase in photosynthetic pigments in PGPB-inoculated plants suggests the capacity of bacterial inoculation to reduce the detrimental effects of salt, by ameliorating the activities of electron transporters associated with photosynthesis [60], as well as the biosynthesis of proteins and enzymes related to pigment stabilization [61].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, all of the strains tested are IAA producers [31,33,49], and this may in part explain the elevated halotolerance detected. As suggested by some authors [50], plant inoculation with halotolerant bacteria strains can represent a good tool to improve plant fitness of salt-sensitive cultivars [51].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Plant growth promoting bacteria, in particular actinobacteria, have been adopted to enhance crop production and alleviate salt stress in several plant species. Actinobacteria have been reported to promote plant growth under salt stress in tomato [ 14 , 15 , 16 , 17 ], soybean [ 18 , 19 ], wheat [ 20 , 21 ], alfalfa [ 22 ], and dwarf glasswort [ 23 ]. Recently, actinobacteria with plant growth promoting potential dwell in extreme saline environments such as marine sediments, mangrove, and halophyte are attracting research attention due to their adaptive features in such environments which are beneficial to plants under salinity stress.…”
Section: Introductionmentioning
confidence: 99%
“…and Nocardiopsis spp. actinomycetes that have already been demonstrated to be used as biostimulants [15] and salt stress-tolerance agents [16]. Given these capabilities, we hypothesized that these strains could be valid biocontrol agents against fungal and bacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%